Treatment patterns and health care resource utilization associated with dalfampridine extended release in multiple sclerosis: a retrospective claims database analysis - Guo A; Grabner M; Palli SR; Elder J; Sidovar M; Aupperle P; Krieger S (Dove Medical Press, 2016)
Amy Guo,1 Michael Grabner,2 Swetha Rao Palli,2 Jessica Elder,1 Matthew Sidovar,1 Peter Aupperle,1 Stephen Krieger3 1Acorda Therapeutics Inc., Ardsley, New York, NY, USA; 2HealthCore Inc., Wilmington, DE, USA; 3Corinne Goldsmith Dickinson Center for MS, Icahn School of Medicine at Mount Sinai, New York, NY, USA Background: Although previous studies have demonstrated the clinical benefits of dalfampridine extended release (D-ER) tablets in patients with multiple sclerosis (MS), there are limited real-world data on D-ER utilization and associated outcomes in patients with MS. Purpose: The objective of this study was to evaluate treatment patterns, budget impact, and health care resource utilization (HRU) associated with D-ER use in a real-world setting. Methods: A retrospective claims database analysis was conducted using the HealthCore Integrated Research DatabaseSM. Adherence (measured by medication possession ratio, or [MPR]) and persistence (measured by days between initial D-ER claim and discontinuation or end of follow-up) were evaluated over 1-year follow-up. Budget impact was calculated as cost per member per month (PMPM) over the available follow-up period. D-ER and control cohorts were propensity-score matched on baseline demographics, comorbidities, and MS-related resource utilization to compare walking-impairment-related HRU over follow-up. Results: Of the 2,138 MS patients identified, 1,200 were not treated with D-ER (control) and 938 were treated with D-ER. Patients were aged 51 years on average and 74% female. Approximately 82.6% of D-ER patients were adherent (MPR >80%). The estimated budget impact range of D-ER was $0.014–$0.026 PMPM. Propensity-score-matched D-ER and controls yielded 479 patients in each cohort. Postmatching comparison showed that the D-ER cohort was associated with fewer physician (21.5% vs 62.4%, P<0.0001) and other outpatient visits (22.8% vs 51.4%, P<0.0001) over the 12-month follow-up. Changes in HRU from follow-up to baseline were lower in the D-ER cohort for metrics including walking-impairment-related hospitalizations and emergency department visits. Conclusion: The majority of D-ER patients were adherent to treatment. D-ER utilization was associated with fewer walking-impairment-related physician and outpatient visits, with lower HRU increase over time. The budget impact of D-ER was low. Keywords: budget impact, costs, real-world, health outcomes, walking impairment